Pencantuman Label Halal Dalam Kemasan Suatu Produk Makanan Dihubungkan Dengan UU Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Mela Septiani (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2017)
Halal (allowed by the Sharia Law, and hereinafter allowed) assurance of food products is a crucial issue for Muslims and becomes a factor in considering whether to buy and consume them or not. The label, for consumers, serve to identify a product, rendering such information of the product as product name, net weight, ingredients, producer’s name and address, expiry date, price, and allowedness. Islam regulates food product allowedness in the Al Quran, stated that Muslims must consume food products which are both allowed and rich in nutrients. The institution which is up to now authorized to certify food product allowedness is the MUI. Inclusion of the halal label in the packaging of a food product will be examined in relation to the Consumer Protection Act and includes how the role and monitoring mechanism carried out by the government on information on halal products circulating in the market. This research is normative legal research with the research methodology used is descriptive analytical. This type of research uses normative juridical which is used to explore information and implementation that legal protection is not merely a set of rules. Legal data in the form of primary, secondary and tertiary legal materials and other legal materials are collected through literature studies and interviews, then the data obtained is analyzed qualitatively juridically. Based on the results of the study, it was found that the license for the inclusion of a product's halal label after obtaining a halal certificate from the MUI, then LPPOM MUI, would issue a halal label after a product obtained halal certification from MUI. Consumer protection of products on the market is the duty of LPPOM MUI to carry out its supervisory function in collaboration with the Health Office and conduct field checks every 6 months. The West Java Provincial Government ratified Regional Regulation No. 13 of 2015 concerning the Development and Supervision of Hygienic and Halal Goods Products.